CASP solutions for planning in hybrid domains. Issue 4 (4th July 2017) - BALDUCCINI, MARCELLO; MAGAZZENI, DANIELE; MARATEA, MARCO; LEBLANC, EMILY C.
Abstract: Constraint answer set programming (CASP) is an extension of answer set programming that allows for numerical constraints to be added in the rules. PDDL+ is an extension of the PDDL standard language of automated planning for modeling mixed discrete-continuous dynamics. In this paper, we present CASP solutions for dealing with PDDL+ problems, i.e., encoding from PDDL+ to CASP, and extensions to the algorithm of theezcsp CASP solver in order to solve CASP programs arising from PDDL+ domains. An experimental analysis, performed on well-known linear and non-linear variants of PDDL+ domains, involving various configurations of theezcsp solver, other CASP solvers, and PDDL+ planners, shows the viability of our solution.